An economists’ Manifesto on unemployment in the European Union - F. MODIGLIANI; J.-P. FITOUSSI; B. MORO; D. SNOWER; R. SOLOW; A. STEINHERR; P. SYLOS LABINI (PSL Quarterly Review, 1998)
In this Manifesto, we make a set of proposals to fight unemployment in the EU. We believe that the European unemployment problem needs to be attacked on two fronts: through a broad spectrum of supply-side policies and the demand management policy. The expansion of aggregate demand is necessary to increase both investment and employment. However, unless supply-side measures are also taken, demand expansion can result in more inflation instead of more employment, because of the mismatch between the demand and supply of labour. What is important to stress is that both demand and supply-side policies must be adopted together by all European countries, in order both to avoid beggar-thy-neighbor problems and, at the same time, to catch all the possible complementary effects of these policies.